Consumer Preference on Instant Noodles in Kathmandu City - Amatya, Kailash Patendra (Management Dynamics, 2019)
This paper attempts to measure customer preference on instant noodles in Kathmandu City. Descriptive and causal research design was used. 100 samples were taken through structured questionnaires. Convenient sampling was used. Descriptive and correlation analysis was done to analyse the data and to test the hypothesis. This study confirmed that brand, price, quality, taste, easy and fast and availability is factors for purchasing noodles in Kathmandu City.